Comparative seroreactivity of piroplasm antigens of Theileria annulata - DUTTA, B; BANSAL, G C; RAY, D; GHORUI, S K (The Indian Journal of Animal Sciences, 2013)
Host cell free piroplasms of Theileria annulata were disrupted by repeated freezing (- 196Â°C) and thawing (37Â°C) to obtain soluble protein antigen of the parasite (fraction I). The insoluble cellular precipitates were sequentially extracted first with Triton x 100 (fraction II) and then with Nonidet P-40 (fraction III). The fraction I showed highest seroreactivity in ELISA when tested against bovine antisera with optimum concentrations of antigens and antibodies. Slab gel electrophoresis of fractionated antigens revealed negligible contamination of host cellular protein. The presence of the major immunodominant proteins of 32.5 and 97 KDa molecular weight was most conspicuous in fraction I.